341 POOR IMPLEMENTATION OF PERIOPERATIVE BETA-BLOCKERS IN ORTHOPEDIC PATIENTS. (1st January 2006) - Ray, M.; Graham, R. M.; Lewis, J. B.; Ryder, K. M.
Abstract : BACKGROUND: Beta-blockers (BBs) reduce the risk of perioperative ischemia and long-term cardiac events. Upcoming quality measures from the Surgical Care Improvement Project (SCIP) will include BB use in the perioperative period. Previous work has demonstrated that BBs are not started in a large majority of patients in the perioperative period. However, nothing is known regarding the actual implementation of BBs: initiation, receipt on the OR day, and continuation in the immediate postoperative period. We investigate implementation of BBs in orthopedic patients with cardiac risks. Methods: This was a retrospective, descriptive chart review study of all orthopedic patients 60 years and greater admitted for nonelective surgery between 1/1/2004 and 12/31/2004. We excluded patients for whom surgery was brief or low risk (ie, wound débridement, metacarpal fixation, closed reduction). BB candidates were patients with cardiac risks chosen by BB clinical trials. These were one or more Lee criteria or 2 or more risks as established by Mangano et al. They could not have contraindications to BBs as established by these clinical trials. Results: There were 125 patients, of which 100 had an indication for BB use. Three of the 100 had documented contraindications for its use, leaving 97/125 candidates (77.6%). Of these 97, the average age was 69.8 years. 60.4% were female, 50.0% were black, and 47.9% were white; 59.4% had a preoperative medicine consult. Mechanism of injury was same height fall (39.6%), fall from height (8.3%), and MVA (46.9%). Fracture site was usually hip and femur (46.9%), tib/fib knee and ankle (33.2%), and upper extremity (16.7%). Altogether, 64/97 (66.0%) had BB ordered appropriate with indications; only 25/97 (25.8%) had it given on OR day. Of those 25, 3 had the beta-blocker abruptly discontinued postoperatively. Overall, 22/97 (22.7%) of appropriate candidates received BB as described in clinical trials. Conclusion: BBs, even when indicated, are not being implemented in accordance with clinical trial protocols. Prior works in vascular surgery patients suggest that abrupt discontinuation of BBs in the perioperative period contributes to increased cardiac events. Poor implementation of BBs potentially may have influenced recent findings suggesting that BBs do not prevent overall mortality and events. Further research is needed to identify the causes of and solutions to poor BB implementation.